2016
DOI: 10.2500/ajra.2016.30.4308
|View full text |Cite
|
Sign up to set email alerts
|

A New Oxidative Stress Marker for Thiol-Disulphide Homeostasis in Seasonal Allergic Rhinitis

Abstract: SAR is a disorder that elevates systemic oxidative stress and reduces antioxidant enzyme activities. Our results shed light on the etiopathogenesis of the disease and can help develop new therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Authors have demonstrated that NT levels were significantly lower in patients with benign paroxysmal positional vertigo, seasonal allergic rhinitis, Bell's palsy, obstructive sleep apne and nasal polyposis [53][54][55][56][57].…”
Section: Head and Neck Pathologiesmentioning
confidence: 99%
“…Authors have demonstrated that NT levels were significantly lower in patients with benign paroxysmal positional vertigo, seasonal allergic rhinitis, Bell's palsy, obstructive sleep apne and nasal polyposis [53][54][55][56][57].…”
Section: Head and Neck Pathologiesmentioning
confidence: 99%
“…Demonstrating the destructive effects of oxidative stress can elicit valuable information in terms of understanding the biochemical process involved in many diseases [14][15][16]. The TDH measurement method newly developed by Erel et al [8,15,[17][18][19][20][21][22] has been shown to a reliable indicator in showing oxidative stress.…”
Section: The European Research Journal Volume 5 Issue 2 March 2019mentioning
confidence: 99%
“…In the process of AR, the antigens have been shown to induce human nasal epithelial cells to produce ROS that trigger cytokine production in AR, and ROS were overproduced and then induced an imbalance between the ROS and endogenous antioxidants or antioxidant enzymes. The overproduced ROS were able to directly or indirectly damage the nasal mucosa, which results in mucosa dysfunction and histological changes [22]. …”
Section: Discussionmentioning
confidence: 99%